We the American people - Stewart, Marguerite Ann (The John Day Company, 1951)
All get along pretty well together, too. This is something that puzzles people in other countries. When that Polish mayor of St. Cloud was visiting Germany, the question most frequently asked him there was how we all managed to live so peaceably together in American.